Effects of long-term blood pressure lowering and dual antiplatelet therapy on cognition in patients with recent lacunar stroke: Secondary Prevention of Small Subcortical Strokes (SPS3) trial The SPS3 Investigators - Pearce, Lesly A. (Lancet Neurol, 2014)
BACKGROUND: The primary outcome results for the Secondary Prevention of Small Subcortical Strokes (SPS3) trial suggested that a lower target blood pressure may be beneficial (19% nonsignificant reduction) for reducing risk of recurrent stroke but that addition of clopidogrel to aspirinwas not. Whether blood pressure (BP) reduction and dual antiplatelet therapy affectchanges in cognition over time in patients with cerebral small vessel disease is unclear. METHODS: Pre-specified secondary endpoint analyses of the SPS3 trial involving 3020 patients, mean age 63 years, with recent symptomatic lacunar infarcts randomized 1:1 to two target levels of systolic BP (130-149 mm Hg vs. <130 mm Hg, open-label) and 1:1 to aonce-dailyantiplatelet therapy (75 mg clopidogrel plus 325 mg aspirin vs. 325 mg aspirin alone, double-blind) during 2003-2011 at 81 centers. The primary cognitive outcome was change in Cognitive Abilities Screening Instrument (CASI) during follow-up. Patients were tested annually (median 3 years of follow-up, maximum5)during which the mean difference in systolic BP averaged 11 mmHg between the two target (138 mm Hg vs 127 mm Hg at 1 year). This study is registered with ClinicalTrials.gov, number NCT 00059306. FINDINGS: The 2916 participants with CASI scores at study entry are included in the analysis.Mean (SD) changes in CASI z-scores from study entry to assessment at years1 (n=2699), 2 (n=2251), 3 (n=1785), 4( n=1134) and 5 (n=803) were 0.11 (0.84), 0.15 (0.85), 0.15 (0.97), 0.19 (1.0), and 0.16 (1.2), respectively. Changes in CASI z-scores over time did not differ between assigned antiplatelet groups (p=0.9) or between assigned blood pressure control groups (p=0.5).There was no interaction between assigned antiplatelet groups and assigned blood pressure control groups and change over time. (p=0.2) INTERPRETATION: Cognitivefunctionis not influenced by short-term treatment with dual antiplatelet therapy or blood pressure reduction in relatively young patients with recent lacunar stroke. Future studies of the effects of blood pressure reduction on cognition should focus on patients with higher rates of cognitive decline.